PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENANGGULANGI MASALAH EKSPLOITASI PEKERJA ANAK DI MALAWI - Putri, Shasa Tania; Retnaningsih, Umi O. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The phenomenon of exploitation of child labour is a global problem that still exists today. In Malawi, many children are involved as child labourers. The majority of these child labourers work in the agricultural sector, especially in the tobacco sector. The problem is because of the type of work that the children do, where the tobacco sector is ad dangerous environment for children. One of the factors that causes the phenomenon of child labour is poverty.This study was written using the theory of international organizations, where the actor involved in this research problem is the International Labour Organization (ILO). This research was also investigated with qualitative research methods. The sources and data used by the author in this study are based on books, journals and other online literature such as reports, newspapers and articles on the ILO's official website.The problem of child labour certainly requires attention from the Government, Non-Governmental Organizations, and even International Organizations, if it is felt that the handling at the government level is not optimal. Therefore, the ILO, as an international labour organization, is here to address this issue. From the results of this study, several contributions that have been made by the ILO are by collaborating with the Japan Tobacco International (JTI) company, to create an educational program, namely ARISE. Another contribution is to hold a Training of Trainers program, which aims to educate the farmers about the management of savings and loan cooperatives there.Key Words: International Organizations, ILO, Child Labour, Tobacco